Forecasting the sales of console games for the Italian market - Rossetti, Renato (Prognozowanie sprzedaży gier konsolowych na rynek włoski, 2019)
In videogames industry, time series analysis can be very useful in determining the general evolution and behaviour of the market dynamics. These methods are applicable to any time series forecasting problem, regardless of the application sector. This article discusses time series approaches to forecast the sales of console games for the Italian market. In particular two univariate techniques were evaluated, exponential smoothing and the SARIMA technique. The aim is to exploit the capabilities of these statistical methods in order to have a comparison of the results and to choose the most accurate model through an ex-post evaluation. Using monthly time-series data from November 2005 to September 2017, the selection of the most suitable model was indicated by the smallest value of the measures of accuracy (MAPE, sMAPE, RMSE) for the out-of-sample observations regarding the period October 2017-September 2018. The implementation of the models was done using Forecast PRO and Gretl. The time series involved is related to the sales regarding the first party manufacturers of consoles and handhelds (Microsoft, Sony and Nintendo)
Econometrics = Ekonometria, 2019, Vol. 23, No. 3, s. 76-88
Keywords: exponential smoothing; SARIMA; forecast; videogames; wygładzanie wykładnicze; prognozy; gry wideo